2005
DOI: 10.1167/iovs.05-0344
|View full text |Cite
|
Sign up to set email alerts
|

SOD2 Protects against Oxidation-Induced Apoptosis in Mouse Retinal Pigment Epithelium: Implications for Age-Related Macular Degeneration

Abstract: The results demonstrate a critical role of SOD2 in protection against oxidative challenge. Cells from HET mice showed greater apoptotic cell death, whereas in those from HEMI mice, cell death induced by oxidative injury was suppressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 34 publications
1
77
0
1
Order By: Relevance
“…Animal experiments showed that manganese SOD2 knockdown in mice resulted in apoptotic death of RPE cells, which was similar to the eyes of patients with AMD [21]. SOD2 protects against oxidation-induced apoptosis in mouse RPE [22]. This implies that SOD may be an important antioxidative enzyme in protecting RPE against oxidant-induced damage.…”
Section: Discussionmentioning
confidence: 90%
“…Animal experiments showed that manganese SOD2 knockdown in mice resulted in apoptotic death of RPE cells, which was similar to the eyes of patients with AMD [21]. SOD2 protects against oxidation-induced apoptosis in mouse RPE [22]. This implies that SOD may be an important antioxidative enzyme in protecting RPE against oxidant-induced damage.…”
Section: Discussionmentioning
confidence: 90%
“…SOD2 overexpression eliminates pro-oxidantinduced mitochondrial ROS in PC-12 cells and decreases cell injury (Pias et al, 2003). Similarly, in retinal pigment epithelial cells, the gene dosage of SOD2 directly relates to the degree of mitochondrial injury and apoptosis induced by H 2 O 2 (Kasahara et al, 2005). In hemopoietic cells, SOD2 transgene decreases ionizing radiation-induced mitochondrial membrane permeability, cytochrome c release and caspase-3 activation (Guo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in SOD 1 have features typical of AMD, older mice exhibited drusen accumulation, thickened Bruch's membrane and choroidal neovascularization (Imamura et al, 2006). SOD 2 was shown to protect against oxidation induced apoptosis in RPE cells from wild type, hemizygous and heterozygous SOD 2 mice (Kasahara, et al, 2005). Reddy et al (2004) found that in SOD 2 deficient lens epithelial cells challenged with superoxide there were dramatic mitochondrial changes, cytochrome C leakage, caspase 3 activation and increased apoptotic death.…”
Section: Mitochondrial Protective and Repair Systemsmentioning
confidence: 99%